Evaluación de la calidad de los certificados de defunción del Hospital Amor de Patria, de San Andrés Islas, Colombia, en 2014 - Carlos Andrés Montalvo-Arce; Yendi Shandira Kelly-Forbes (Universidad de Antioquia, 2018)
Introduction: The quality of the medical death certificate in the 'causes' section is of fundamental importance in public health, in addition to its ethical, medico-legal and juridical consequences. Objective: To evaluate the completion quality of the death certificates and the causes recorded at the Amor de Patria Hospital on the island of San Andrés (Colombia). Methodology: Cross-sectional descriptive study, using non-probability sampling for convenience of year selection. The evaluation categories were defined: "causes of death", "direct cause", "intermediate cause", "basic cause of death", "other pathological states" and "sequence". Additionally, a review of the completion quality of the causes of death was carried out from two points of view: the structure and consistency of the diagnoses completed on the death certificate. Calculation was made of the proportions of typed errors, consistency and kappa statistic for the causes according to the 6/67 list of the Pan American Health Organization. Results: 172 death certificates were completed. According to the place of death, 131 deaths occurred in the health institution and 41 at home; in 9.9% an error of basic cause was identified, and in 10.5% the absence of the sequence; there was consistency in the basic cause in 55.9% of the certifications. Conclusion: It is necessary to enhance the training of institutional human talent in the certification of vital facts, given the identification of error in 28% of death certificates, with a moderate consistency in the causes of death, with a kappa statistic of 0.58.